THE PSYCHOLOGICAL BENEFITS OF MINDFULNESS AND ITS IMPACT ON WELL-BEING - Pedro Silva; Clara Mendes; Jamil Khan (Yayasan Adra Karima Hubbi, 2026)
Mindfulness, the practice of paying focused attention to the present moment without judgment, has been shown to improve psychological well-being. As mental health concerns grow worldwide, mindfulness is gaining attention as a tool to enhance emotional regulation, reduce stress, and foster greater resilience. This study aims to investigate the psychological benefits of mindfulness and its influence on overall well-being. Specifically, it seeks to assess how regular mindfulness practice contributes to improvements in mental health, emotional stability, and life satisfaction. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews. Data were collected from 300 participants who engaged in an 8-week mindfulness intervention. The Perceived Stress Scale (PSS) and the Mental Health Continuum-Short Form (MHC-SF) were used to measure stress levels and overall well-being before and after the intervention. Semi-structured interviews were also conducted to gather personal experiences. The findings revealed significant reductions in perceived stress and improvements in mental well-being. Participants reported feeling more emotionally balanced, present, and connected to their surroundings. This study concludes that mindfulness significantly benefits psychological well-being by reducing stress and improving emotional health. Incorporating mindfulness into daily routines can be a valuable tool for enhancing mental health.